Pengaruh Financial Literacy, E-Money, Gaya Hidup Konsumtif dan Financial Distress Terhadap Perilaku Pengelolaan Keuangan Pribadi Gen Z di Moderasi dengan Mental Accounting Sebagai Variabel Moderasi - Risma Handayani Istiqomah; Enggar Nursasi (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This research aims to analyze the influence of financial literacy, E-Money usage, consumptive lifestyle, and financial distress on the financial management behavior of Generation Z students, with mental accounting as a moderating variable. Using a quantitative approach, data were collected from 93 active students via an online questionnaire and analyzed using PLS-SEM with SmartPLS 4.0. The results show that financial literacy, E-Money, and consumptive lifestyle have a significant effect on financial management behavior, while financial distress does not. Mental accounting significantly moderates the effect of financial literacy, E-Money, and consumptive lifestyle on financial behavior, but does not moderate the effect of financial distress. These results emphasize the role of mental accounting as a behavioral control mechanism the strengthen financial discipline among Generation Z in the digital era.